A Fermi‐Level‐Pinning‐Free 1D Electrical Contact at the Intrinsic 2D MoS2–Metal Junction. Issue 25 (8th May 2019) - Yang, Zheng; Kim, Changsik; Lee, Kwang Young; Lee, Myeongjin; Appalakondaiah, Samudrala; Ra, Chang‐Ho; Watanabe, Kenji; Taniguchi, Takashi; Cho, Kyeongjae; Hwang, Euyheon; Hone, James; Yoo, Won Jong
Abstract: Currently 2D crystals are being studied intensively for use in future nanoelectronics, as conventional semiconductor devices face challenges in high power consumption and short channel effects when scaled to the quantum limit. Toward this end, achieving barrier‐free contact to 2D semiconductors has emerged as a major roadblock. In conventional contacts to bulk metals, the 2D semiconductor Fermi levels become pinned inside the bandgap, deviating from the ideal Schottky–Mott rule and resulting in significant suppression of carrier transport in the device. Here, MoS2 polarity control is realized without extrinsic doping by employing a 1D elemental metal contact scheme. The use of high‐work‐function palladium (Pd) or gold (Au) enables a high‐quality p‐type dominant contact to intrinsic MoS2, realizing Fermi level depinning. Field‐effect transistors (FETs) with Pd edge contact and Au edge contact show high performance with the highest hole mobility reaching 330 and 432 cm 2 V −1 s −1 at 300 K, respectively. The ideal Fermi level alignment allows creation of p‐ and n‐type FETs on the same intrinsic MoS2 flake using Pd and low‐work‐function molybdenum (Mo) contacts, respectively. This device acts as an efficient inverter, a basic building block for semiconductor integrated circuits, with gain reaching 15 at V D = 5 V. Abstract : Polarity control of MoS2 is realized without extrinsic doping by employing a Fermi‐level‐pinning‐free 1D metal contact design. The use of high‐work‐function metals such as Pd and Au gives rise to high‐performance p‐type MoS2 with hole mobility exceeding 400 cm 2 V −1 s −1 at 300 K. The pinning factor obtained from MoS2 1D contact devices approaches the ideal Schottky–Mott limit.